2008
DOI: 10.1200/jco.2007.12.3588
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Lapatinib for Brain Metastases in Patients With Human Epidermal Growth Factor Receptor 2–Positive Breast Cancer

Abstract: Purpose-One third of women with advanced human epidermal growth factor receptor 2 (HER-2)-positive breast cancer develop brain metastases; a subset progress in the CNS despite standard approaches. Medical therapies for refractory brain metastases are neither well-studied nor Authors' disclosures of potential conflicts of interest and author contributions are found at the end of this article. AUTHORS' DISCLOSURES OF POTENTIAL CONFLICTS OF INTERESTAlthough all authors completed the disclosure declaration, the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
251
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(264 citation statements)
references
References 34 publications
6
251
0
3
Order By: Relevance
“…In this study, 10 patients had brain metastases at baseline and of these 8 experienced either systemic PR or SD, indicating that lapatinib monotherapy is efficacious in HER2-positive BC patients with brain metastases, thus supporting previous reports (Lin et al, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…In this study, 10 patients had brain metastases at baseline and of these 8 experienced either systemic PR or SD, indicating that lapatinib monotherapy is efficacious in HER2-positive BC patients with brain metastases, thus supporting previous reports (Lin et al, 2008).…”
Section: Discussionsupporting
confidence: 75%
“…More recently, there have been further reports of responses to lapatinib-based therapy. After an initial singlecentre phase II study of lapatinib monotherapy in patients with HER2-positive breast cancer who developed progressive CNS metastases after prior loco-regional therapy (Lin et al, 2008), a larger multicentre phase II study involving 242 patients reported a 6% CNS ORR to lapatinib alone (Lin et al, 2009). In an exploratory analysis, a further 21% patients experienced a X20% volumetric reduction in CNS lesions, with many having significant improvement in neurological symptoms.…”
Section: Pre-treatmentmentioning
confidence: 99%
“…A phase II study with single agent lapatinib 750 mg bid was undertaken in patients with HER2-positive CNS metastases who had shown progression in their brain after earlier whole-brain radiotherapy (WBRT), and clinical and radiological responses were observed (Lin et al, 2008). Subsequently, a larger multicentre phase 2 study involving 242 patients recently reported a 6% CNS objective response rate to lapatinib alone (defined as X50% volumetric reduction of CNS lesion(s) (Lin et al, 2009).…”
mentioning
confidence: 99%
“…Therefore, clinically, BMs are a highly relevant problem. Despite this, only limited data are available for opti mal treatment strategies in breast cancer patients, since most studies on BMs involved other tumor entities [30][31][32][33][34][35][36]. It is therefore encouraged to register patients with central nervous system (CNS) metastases diagnosed in Germany retrospec tively and prospectively in a collaborative registry study.…”
Section: Central Nervous System Metastases In Breast Cancermentioning
confidence: 99%